2007
DOI: 10.1101/gad.1609907
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene addiction: setting the stage for molecularly targeted cancer therapy

Abstract: In pugilistic parlance, the one-two punch is a devastating combination of blows, with the first punch setting the stage and the second delivering the knock-out. This analogy can be extended to molecularly targeted cancer therapies, with oncogene addiction serving to set the stage for tumor cell killing by a targeted therapeutic agent. While in vitro and in vivo examples abound documenting the existence of this phenomenon, the mechanistic underpinnings that govern oncogene addiction are just beginning to emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
326
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(333 citation statements)
references
References 207 publications
(143 reference statements)
7
326
0
Order By: Relevance
“…In general, IGFBP7 induced apoptosis in human cancer cell lines that had an activating mutation in BRAF or RAS, and that were sensitive to chemical inhibition of BRAF-MEK-ERK signaling. Previous studies have shown that cancer cells harboring an activated BRAF mutation are highly dependent on BRAF-MEK-ERK signaling for proliferation and survival (13), and that BRAF mutation predicts sensitivity to MEK inhibition (14). These findings provide the rationale for developing therapeutic strategies that target the BRAF-MEK-ERK signaling pathway for treatment of melanoma and other cancers in which BRAF is mutated (13).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, IGFBP7 induced apoptosis in human cancer cell lines that had an activating mutation in BRAF or RAS, and that were sensitive to chemical inhibition of BRAF-MEK-ERK signaling. Previous studies have shown that cancer cells harboring an activated BRAF mutation are highly dependent on BRAF-MEK-ERK signaling for proliferation and survival (13), and that BRAF mutation predicts sensitivity to MEK inhibition (14). These findings provide the rationale for developing therapeutic strategies that target the BRAF-MEK-ERK signaling pathway for treatment of melanoma and other cancers in which BRAF is mutated (13).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that cancer cells harboring an activated BRAF mutation are highly dependent on BRAF-MEK-ERK signaling for proliferation and survival (13), and that BRAF mutation predicts sensitivity to MEK inhibition (14). These findings provide the rationale for developing therapeutic strategies that target the BRAF-MEK-ERK signaling pathway for treatment of melanoma and other cancers in which BRAF is mutated (13). Inhibitors of BRAF have been developed but unfortunately have done poorly in clinical trials (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of tumor suppressor genes through deletion, inactivating mutations or epigenetic silencing results in the removal of restraints of the cell and ultimately leads to tumorigenesis [84]. The evolution of a benign to an invasive and metastatic tumor is progressively driven by the accumulation of alterations in these genes with highly diverse functions [85]. Recently, a third theme has been investigated and emerged as possible target in cancer therapy.…”
Section: Addictions Of Cancer Cells Oncogene Addiction and Tumor Suppmentioning
confidence: 99%
“…An implication of this difference in addiction between normal cells and tumor cells is that when the associated path ways involved are blocked, detrimental effects on the proliferation of cancer cells are expected while at the same time normal cells remain relatively unaffected. This difference between tumor cells and normal cells is crucial for effective cancer treatment with acceptable toxicity [85]. Understanding the molecular details of oncogene addiction is crucial for the design of targeted to therapies that successfully prolong a patient's life and prevent escape from treatment.…”
Section: Doi: 107243/2052-6199-1-7mentioning
confidence: 99%
“…Tumor cells do encode proteins, on which they are totally dependent -that is, the downregulation or functional inhibition of such components causes tumor cell death. The inactivation of such a component in normal cells is often tolerated and has led to the concept of " tumor cell oncogene addiction " [8] . Such proteins appear as appealing drug targets, and the development of inhibitors of oncogenic kinases -such as members of the EGF receptor family, BCR -ABL, PDGF receptor or c -KIT -has led to most impressive clinical advances.…”
Section: Discovery Of New Potential Drug Targets and The Limitations mentioning
confidence: 99%